WHAT SHAPES TAXPAYER BEHAVIOUR? A BIBLIOMETRIC EXPLORATION OF TAX INCENTIVES, TAX DEDUCTION, AND TAX RELIEF - Mohamed Ariffin, Umikalsom; Abdul Hamid , Suhaila; Muhammad , Izlawanie (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
This study examines the global research landscape surrounding the factors that influence taxpayer behaviour, with a specific focus on tax incentives, tax deductions, and tax relief. Governments widely employ these fiscal tools to influence compliance, stimulate economic growth, and support social development. Nonetheless, academic inquiry into their behavioral impact remains fragmented. The primary aim of this research is to provide a comprehensive bibliometric analysis of scholarly output in this domain and to identify key trends, thematic clusters, and collaborative networks within it. The central problem addressed is the lack of a consolidated understanding of how these tax mechanisms have been studied globally, as well as the existing gaps, particularly in developing countries. Using Scopus as the primary data source, a total of 825 peer-reviewed documents published between 2000 and 2025 were extracted through a keyword search strategy that included the terms “Tax Incentives,” “Tax Deduction,” and “Tax Relief.” The data were cleaned using OpenRefine and visualised through VOSviewer for co-authorship, keyword co-occurrence, and citation analysis. Results show that the United States, China, and the United Kingdom are the leading contributors, with “Tax Incentives” being the most frequently occurring keyword. Key thematic areas include investment promotion, corporate tax avoidance, Research and Development (R&D) support, and emerging links to sustainability and innovation. Although Malaysia ranks 12th in publication output, its contribution remains modest. This reveals a significant research gap in the Malaysian context, where extensive use of tax incentives is prevalent in policy practice, yet empirical and behaviour-focused academic studies are limited. In conclusion, this bibliometric review highlights a growing and diversifying research interest in tax-based behavioural tools. It underscores the urgent need for more context-specific studies in Malaysia to support evidence-based policymaking and optimise the effectiveness of fiscal instruments.